Cultures and Traditions of Wordplay and Wordplay Research - Winter-Froemel, Esme (The Dynamics of Wordplay, 2018)
This volume focuses on realisations of wordplay in different cultures and social and historical contexts, and brings together various research traditions of approaching wordplay. Together with the volume DWP7, it assembles selected papers presented at the interdisciplinary conference The Dynamics of Wordplay / La dynamique du jeu de mots (Trier, 2016) and stresses the inherent dynamicity of wordplay and wordplay research.